2009
DOI: 10.1002/pmic.200800589
|View full text |Cite
|
Sign up to set email alerts
|

Secretome analysis of differentially induced proteins in rice suspension‐cultured cells triggered by rice blast fungus and elicitor

Abstract: Secreted proteins were investigated in rice suspension-cultured cells treated with rice blast fungus Magnaporthe grisea and its elicitor using biochemical and 2-DE coupled with MS analyses followed by their in planta mRNA expression analysis. M. grisea and elicitor successfully interacted with suspension-cultured cells and prepared secreted proteins from these cultures were essentially intracellular proteins free. Comparative 2-D gel analyses identified 21 differential protein spots due to M. grisea and/or eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 37 publications
2
78
0
5
Order By: Relevance
“…Modeling the dynamics of the 2245 features across the two treatments and three time points allowed features to be grouped into six distinct expression profiles (profiles I to VI), of which the largest group, termed profile I, corresponded to 720 features that showed a strong increase in accumulation at 2 DAI with a reduction at the 4 and 6 DAI time points ( Figure 5B; see Supplemental Data Set 1 online). Within this category were a large proportion of genes representative of basal defense with some of them already well characterized during leaf infection (Table 1); for example, an endochitinase (Chit1; Kim et al, 2009), an elicitor-inducible shikimate kinase (SK2; Kasai et al, 2005), certain members of the WRKY family (WRKY71, Chujo et al, 2008;WRKY53, Chujo et al, 2009), or noteworthy, the previously described chitin receptor (chitin-elicitor binding protein, CEBiP; Kaku et al, 2006), a Ser/Thr protein kinase previously reported to be associated with defense against biotrophic rust fungi in other cereals (ORK10; Cheng et al, 2002b), and NAC4, a transcriptional activator involved in the initiation of hypersensitive response-associated cell death (Kaneda et al, 2009). The distinct gene expression pattern was independently confirmed by real-time RT-PCR (see Supplemental Figure 1 online).…”
Section: Root Invasion By M Oryzae Is Accompanied By Suppression Of mentioning
confidence: 99%
“…Modeling the dynamics of the 2245 features across the two treatments and three time points allowed features to be grouped into six distinct expression profiles (profiles I to VI), of which the largest group, termed profile I, corresponded to 720 features that showed a strong increase in accumulation at 2 DAI with a reduction at the 4 and 6 DAI time points ( Figure 5B; see Supplemental Data Set 1 online). Within this category were a large proportion of genes representative of basal defense with some of them already well characterized during leaf infection (Table 1); for example, an endochitinase (Chit1; Kim et al, 2009), an elicitor-inducible shikimate kinase (SK2; Kasai et al, 2005), certain members of the WRKY family (WRKY71, Chujo et al, 2008;WRKY53, Chujo et al, 2009), or noteworthy, the previously described chitin receptor (chitin-elicitor binding protein, CEBiP; Kaku et al, 2006), a Ser/Thr protein kinase previously reported to be associated with defense against biotrophic rust fungi in other cereals (ORK10; Cheng et al, 2002b), and NAC4, a transcriptional activator involved in the initiation of hypersensitive response-associated cell death (Kaneda et al, 2009). The distinct gene expression pattern was independently confirmed by real-time RT-PCR (see Supplemental Figure 1 online).…”
Section: Root Invasion By M Oryzae Is Accompanied By Suppression Of mentioning
confidence: 99%
“…2). In previous reports, OsRLK and OsTLP were identified as secreted proteins in rice SCCs treated with the rice blast fungus Magnaporthe grisea and its elicitor using secretome analysis (Kim et al, 2009) and also highly induced in the incompatible interaction, compared to the compatible interaction (Kim et al, 2004a). OsPR-10 was expressed in developmental tissues, including the flower and root (Kim et al, 2008b) and was also expressed under environmental stresses such as rice blast fungus/fungal elicitor, wounding, senescence, and phytohormone application (Kim et al, 2003b(Kim et al, , 2004a(Kim et al, , 2008b.…”
Section: Resultsmentioning
confidence: 94%
“…Several studies have examined proteins induced during Magnaporthe-rice interactions for example (Kim et al 2009). The difficulty in obtaining a complete picture of proteins involved in the Magnaporthe-rice interaction results from the complexity of the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteomic studies have identified Magnaporthe or rice proteins induced during infection (Kim et al 2003(Kim et al , 2004(Kim et al , 2009, although in rice there is a general lack of information on extracellular proteins. The examination of sub-cellular proteomes can give more specific and relevant information about biological processes than whole extract studies e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation